Anemia among indigenous women in Brazil: findings from the First National Survey of Indigenous People's Health and Nutrition. Issue 1 (December 2015) - Borges, Maria; Buffarini, Romina; Santos, Ricardo; Cardoso, Andrey; Welch, James; Garnelo, Luiza; Coimbra, Carlos; Horta, Bernardo
Abstract Background Anemia is recognized as a major public health problem that disproportionately affects vulnerable populations. Indigenous women of reproductive age in Brazil are thought to be at high risk, but lack of nationwide data limits knowledge about the burden of disease and its main determinants. This study aimed to assess the prevalence of anemia and associated factors in this population using data from The First National Survey of Indigenous People's Health and Nutrition in Brazil. Methods Data were collected from Indigenous women between 15 and 49 years old based on a nationwide sample of villages. The outcomes of interest were hemoglobin levels (g/dL) and anemia (< 12 g/dL for nonpregnant and < 11 g/dL for pregnant women). Multilevel models were used to explore associations with contextual (village) and individual (household/woman) level variables. Results Based on data for 6692 Indigenous women, the nationwide mean hemoglobin level was 12.39 g/dL (95 % CI: 12.29–12.50). Anemia prevalence was high (33.0 %; 95 % CI: 30.40–35.61 %) and showed pronounced regional disparities. No village-level characteristics were associated with anemia or hemoglobin levels in the multilevel model. Even after controlling for upper level variables, socioeconomic status, parity, body mass index, and having been treated for malaria were associated with anemia and hemoglobin levels. Conclusion The prevalence of anemia in Brazilian Indigenous women was 12 % greater than the national estimates for women of reproductive age. Anemia prevalence and mean hemoglobin levels among Indigenous women appear to be partly explained by some previously recognized risk factors, such as socioeconomic status, body mass index, and malaria; however, part of the variability in these outcomes remains unexplained. Knowledge of health status and its potential determinants is essential to guide public policies aimed at controlling anemia burden in Indigenous communities.